Fetal sexual dimorphism of maternal thyroid function parameters during pregnancy, a single center retrospective real-world study - Wu, Meiqin; Hu, Chunping; Huang, Dan; Ying, Hao; Hua, Jing (Frontiers in Endocrinology, 2024)
Thyroid function during pregnancy fluctuates with gestational weeks, seasons and other factors. However, it is currently unknown whether there is a fetal sex-specific thyroid function in pregnant women. The purpose of this study was to investigate the fetal sex differences of maternal thyroid-stimulating hormone (TSH) and free thyroxine (FT4) in pregnant women. This single-center retrospective real-world study was performed by reviewing the medical records of pregnant women who received regular antenatal health care and delivered liveborn infants in Shanghai First Maternity and Infant Hospital (Pudong branch), from Aug. 18, 2013 to Jul. 18, 2020. Quantile regression was used to evaluate the relationship between various variables and TSH and FT4 concentrations. The quantile regression also evaluated the sex impact of different gestational weeks on the median of TSH and FT4. A total of 69,243 pregnant women with a mean age of 30.36 years were included. 36197 (52.28%) deliveries were boys.In the three different trimesters, the median levels (interquartile range) of TSH were 1.18 (0.66, 1.82) mIU/L and 1.39 (0.85, 2.05) mIU/L, 1.70 (1.19, 2.40) mIU/L; and the median levels (interquartile range) of FT4 were 16.63 (15.16, 18.31) pmol/L, 14.09 (12.30, 16.20) pmol/L and 13.40 (11.52, 14.71) pmol/L, respectively. The maternal TSH upper limit of reference ranges was decreased more in mothers with female fetuses during gestational weeks 7 to 12, while their FT4 upper limit of the reference ranges was increased more than those with male fetuses. After model adjustment，the median TSH level was 0.11 mIU/L lower (P <0.001), and FT4 level was 0.14 pmol/L higher (P <0.001) for mothers with female fetuses than those with male fetuses during gestational weeks 9 to 12. We identified sexual dimorphism in maternal thyroid function parameters, especially during 9-12 weeks of pregnancy. Based on previous research, we speculated that it may be related to the higher HCG levels of mothers who were pregnant with girls during this period. However, longitudinal studies are needed to determine if fetal sex differences impact the maternal thyroid function across pregnancy.